2012
DOI: 10.1016/j.maturitas.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

A genetic polymorphism in the CYP19A1 gene and the risk of hypertension among midlife women

Abstract: Objective To test whether a synonymous single nucleotide polymorphism (A→G; rs700518) in the CYP19A1 gene, which encodes the enzyme aromatase, is associated with an increased risk for hypertension of midlife women. Methods In a cross-sectional study, 639 midlife women were recruited. Eligible women had their blood pressure, weight and height measured, and donated a blood sample for hormone and genetic analyses. The participants also completed a detailed study survey. Women were categorized according to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This is not surprising as other investigators reported the same findings for this polymorphism (35). Meanwhile other SNPs in the CYP19A1 gene had also been described to be associated with differences in BMI (36;37).…”
Section: Discussionsupporting
confidence: 83%
“…This is not surprising as other investigators reported the same findings for this polymorphism (35). Meanwhile other SNPs in the CYP19A1 gene had also been described to be associated with differences in BMI (36;37).…”
Section: Discussionsupporting
confidence: 83%
“…Mutations in follicle-stimulating hormone receptors were significantly related to essential hypertension in women (42). Meanwhile, the CYP 19 A1 gene, responsible for the encoding of aromatase enzyme, was associated with hypertension only in women, which was dependent on the BMI (43). Apart from that, hyperactivity of the sympathetic nervous system, coexisting with obesity, indicates this common pathophysiological mechanism in the development of hypertension (44).…”
Section: Discussionmentioning
confidence: 99%
“…There are a series of data available. The rs700518AA genotypes were reported to be associated with some other estrogen-related diseases, such as hypertension 36 and breast cancer. 37 Although CYP19 rs700518A>G is an anonymous variation in exon 3 (Val 80 Val), it may affect posttranscriptional modification, resulting in changes in gene expression and aromatase levels and further affecting estrogen production.…”
Section: Discussionmentioning
confidence: 99%